Bibliometric review on indigenous entrepreneurship: Past findings, present and ways forward - Nor Emmy Shuhada, Derani; Mazita, Mokhtar; Gusman, Nawanir; Haziman, Zakaria (Akademia Baru, 2023)
Indigenous entrepreneurship is one of the emerging academic fields. Studying indigenous entrepreneurship creates a dynamic environment because business and entrepreneurship boost rural and urban socio-economic development. Indigenous people are vital to the entrepreneurial ecosystem. 250–600 million indigenous peoples live worldwide, including Africans, Americans, Asians, Europeans, and Oceanians. The government and policymakers have prioritized economic, social, educational, human capital, health, and development policies at the local and international levels to support indigenous communities. Academic and research activities on indigenous populations are lacking due to their importance. Recent studies only represent specific communities and ethnicities in a given geographic area. This study reviews indigenous entrepreneurship using a bibliometric approach. Bibliometrics was used to retrieve 767 journal articles from WoS. Three analyses were performed: citation analysis, co-citation analysis, and co-word analysis. Co-word analysis finds five clusters, and co-citation analysis four. This study examines indigenous entrepreneurship conceptually and practically and suggests a few future directions based on research limitations.